Trigeminal nerve schwannoma - Kashyap, Prashant; Dave, Dhaval; Melmane, Prashant; Bhate, Archana (International Journal of Research in Medical Sciences, 2016)
Trigeminal schwannomas are uncommon slow growing encapsulated tumours composed of schwann cells. Trigeminal schwannomas are the second most common type of schwannoma, after the far more common acoustic schwannoma. In this case definite diagnosis could not be made after 1 CT (computerized tomography) scan and 3 MRI (magnetic resonance imaging) (outside hospital) but finally after proper clinical examination and discussion with radiologist about the best diagnostic imaging in this case we reached to a diagnosis of trigeminal nerve schwannoma after MRI brain with contrast.